Hygienic coatings by UV curing of diacrylic oligomers with added triclosan (2009)
Hygienic coatings have been obtained by UV photopolymerization of mixtures of urethane-diacrylate, tri-propylene-glycol diacrylate and 2,4,4¢-trichloro-2¢-hydroxydiphenylether (Triclosan). UV-dried coatings containing a weight fraction of Triclosan as low as 0.001 submitted to tests for antimicrobial activity evaluation with Escherichia coli colonies have shown the complete elimination of living bacteria in the thin liquid layer in contact with the film surface. A persistent biocide activity can also be observed after a prolonged water treatment of the coating. The biocide release from the coating has been studied through contact with water–ethanol mixtures of different compositions. The maximum release rate has been observed at an ethanol weight fraction of 0.85, where the crosslinked films show the maximum swelling. The phenomena can be explained on the basis of the interaction between the liquid and the polymer network through the Hansen solubility parameters.